EXPLORATION OF BREADWINNER’S CHALLENGES DURING COVID-19 - Merrylynn, Sulaiman (Universiti Malaysia Sarawak (UNIMAS), 2020)
Breadwinners face different challenges generally, and now more during the COVID-19 pandemic. This study aims to explore the challenges faced by breadwinners during the COVID-19 pandemic in detailed manner. The data collection was semi-structured interviews and analyzed using Interpretative Phenomenological Analysis (IPA). The respondents for this study are three breadwinners currently residing in Kota Kinabalu. The data gained showed that there are no relationship between demography and the challenges. Respondents with similar demographic details faced different challenges while respondents with different demographic details faced similar challenges, showing that the demographic details do not affect the challenges they faced. The issue can be explored in further studies due to the limitations in the study such as limited number of respondents and source of past researches as references. Future researchers can explore more challenges on a more wider range of breadwinners to gain more data and in-depth informations regarding similar topics.